The Effect of Interaction of Hydroalcoholic Extract of Ginger Rhizome (Zingiber Officinale) with Nitric Oxide System on Mechanical Activity of Isolated Trachea of Male Rats - Fereshteh Dadfar; Aminollah Bahaoddini; Seyyed Ebrahim Hoseini (Fasa University of Medical Sciences, 2014)
Background ;Objectives: Ginger is a plant that was used for bronchodilation from the ancient times. The aim of this study was to evaluate the effect of hydroalcoholic extract of Zingiberofficinale on mechanical activity of isolated trachea and its interaction with nitric oxide system. Materials & Methods: 15 adult male rats after adapting with their environment for one week were anesthetized with intraperitoneal injection of sodium pentobarbital and theirs trachea were isolated and divided into 3-mm strips. Then the isolated tracheal strips were divided into control and experimental groups that were inserted to organ bath contained krebs solution. The mechanical activity of trachea was recorded by power lab system. After establishing the basic conditions, in experimental group, hydroalcoholic extract of ginger (0.3mg/ml) and to control group in the same conditions, ethanol 70% as solvent was added. Then, mechanical activity of each group in the presence of L-NAME was recorded. The data were analyzed through paired sample t- test at P ≤ 0.05 as the significant level. Results: The results showed significant decrease of mechanical activity of tracheal strips in the group which was exposed to ginger. These effects were not reversed after administration of L- NAME in comparison with the control group. Conclusion: It can be concluded that ginger has an inhibitory effect on mechanical activity of trachea which is probably independent from nitric oxide system.